From Tree to Fork - The Genipap fruit - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
The tree is an important species for the restoration of Brazilian riparian forests; it has been promoted by the Brazilian government for sustainable timber and fruit harvesting programs.